The value relevance of “assured” environmental disclosure: The Italian experience - Fazzini, Marco; Dal Maso, Lorenzo (Sustainability accounting, management and policy journal (Print), 2016)
Purpose This paper aims to provide insight into how environmental information is reflected in the market value of listed Italian companies. In particular, it investigates the value relevance of voluntary environmental information disclosed by companies and the influence of environmental policies assurance. Design/methodology/approach The method used is the accounting-based valuation model used by Cormier and Magnan (2007), analogue to the one developed by Ohlson (1995), which considers market value of equity as a function of book value, accounting earnings and environmental indicators as provided by Bloomberg. The analysis in this paper is based on the environmental disclosure score (i.e. proxy of a company's transparency in reporting environmental information) and the assurance practice (i.e. whether or not the company's environmental policies were subject to an independent assessment for the reporting period). Findings Results partially support initial conjectures, i.e. the environmental voluntary disclosure represents value-relevant information positively correlated with firms' market value. Furthermore, when such information is subject to an independent assessment for the reporting period, an incremental benefit deriving from the assurance of such information cannot be found. This is similar to the findings of Choet al. (2014), i.e. the market perceptions on assurance may need to be developed before the environmental report assurance market in Italy can develop. Research limitations/implications Limitations are related to the small sample located in a single country, meaning that results may not be generalisable. The implications are that other methods may provide further value, but these may need to be based either on different data or larger samples (i.e. cross-country analysis). Originality/value The increasing importance of environmental issues for economic decision-making and the presence of ethical investors create incentives for environmental information disclosure, which is becoming increasingly significant for comprehensive firm valuation. However, for this information to serve its role, disclosure must be credible. Hence, there are many companies that resort to voluntary assurance of environmental policies, motivated by a need to demonstrate credibility with external stakeholders. Notwithstanding, the influence of verification practice over environmental disclosure on a low regulation country has not yet been completely explored. This paper aims to fill this gap.